Effects of different nutritional plans on broiler performance - Buteri,CB (2009)
An experiment was carried out at the Department of Animal Science of the Federal University of Viçosa, Brazil, to evaluate the effects of different nutritional plans on the performance of male and female Ross broilers. A completely randomized experimental design with a 6x2 factorial arrangement (six nutritional plans x two sexes) with six replicates of 20 birds per experimental unit was applied. The nutritional plans adopted for males and females included 3, 5, or 28 feeds, and the other 3 plans included 28 feeds containing 92.5, 100, and 107.5% of digestible lysine requirements established according to a mathematical model developed exclusively for Ross broilers. The results showed that the tested 28-feed feeding programs are equivalent, and allow similar performance as compared to 3- and 5-feed feeding programs. Based on the lysine levels included in the different nutritional plans, it was possible to fit the equations: Y = -0.0079x + 1.2435 (R² = 0.981) for males and Y = -0.0084x + 1.1925 (R² = 0.978) for females, where "Y" is digestible lysine level (%) and "x" is average age in days. These equations are specific for multiple-phase feeding programs. The performance of male and female broilers fed the lysine levels established by the mathematical models was similar as to that of birds fed the other nutritional plans. This demonstrates that it is possible to determine broiler lysine.